Familial amyloid polyneuropathy (TTR ala 60) in north west Ireland: a clinical, genetic, and epidemiological study. Issue 1 (July 1995) - Reilly, M M; Staunton, H; Harding, A E
Abstract : A cluster of cases of familial amyloid polyneuropathy has been described in Donegal, north west Ireland. Two patients from this region have been shown to have the ala 60 mutation in the transthyretin gene. Three kindreds with this mutation have also been described in the United States. Genealogical and haplotype studies indicate that all known patients with this mutation are related and are descended from a founder in north west Ireland. There is evidence for reduced penetrance of this disorder. A population based study showed that 1.1% of the population in this area in north west Ireland carry the mutation. This has implications in terms of diagnosis, genetic counselling, and treatment in the future.